Red House, Government Buildings, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Exterior view of the Red House located in Port of Spain, Trinidad. There is carriage passing in front the building on Abercromby Street.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Streets--Trinidad and Tobago; Trees--Trinidad and Tobago; Arches--Trinidad and Tobago; Windows--Trinidad and Tobago; Towers--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Horses--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Balconies--Trinidad and Tobago; [1900]; Parliament Building (Trinidad and Tobago); Red House, The (Trinidad and Tobago)